2016
DOI: 10.1038/srep20467
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Mediated Targeting of Cyclosporine A Enhances Cardioprotection Against Ischemia-Reperfusion Injury Through Inhibition of Mitochondrial Permeability Transition Pore Opening

Abstract: Myocardial ischemia-reperfusion (IR) injury limits the therapeutic effects of early reperfusion therapy for acute myocardial infarction (MI), in which mitochondrial permeability transition pore (mPTP) opening plays a critical role. Our aim was to determine whether poly-lactic/glycolic acid (PLGA) nanoparticle-mediated mitochondrial targeting of a molecule that inhibits mPTP opening, cyclosporine A (CsA), enhances CsA-induced cardioprotection. In an in vivo murine IR model, intravenously injected PLGA nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 36 publications
1
73
0
Order By: Relevance
“…Taken together, our data suggest the efficacy of Pitavastatin-NPs on post-infarct LV remodeling was predominantly mediated by its efficacy on inflammatory cells. Similar to the previous reports, 20,21,25) Pitavastatin-NPs showed its efficacy at a lower concentration as compared with an equivalent dose of pitavastatin solution.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Taken together, our data suggest the efficacy of Pitavastatin-NPs on post-infarct LV remodeling was predominantly mediated by its efficacy on inflammatory cells. Similar to the previous reports, 20,21,25) Pitavastatin-NPs showed its efficacy at a lower concentration as compared with an equivalent dose of pitavastatin solution.…”
Section: Discussionsupporting
confidence: 78%
“…In myocardium after ischemia-reperfusion, PLGA nanoparticles distribute in myocardial tissues exposed to ischemia. 20,25) After MI, howev- er, it is speculated that PLGA nanoparticles are hardly delivered to the infarcted myocardium due to disrupted blood flow. Actually, there were no apparent fluorescent signals emitted by FITC-NPs in the infarcted zone of the heart.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous study suggested that pharmacological inhibitor of Cyp-D, cyclosporine-A (CsA), can inhibit MPTP and protect cardiac cells against oxidative stress, hypoxia, and I/R [7,8]. CsA was previously considered as a calcineurin inhibitor that is widely used to prevent acute rejection after liver transplantation [9].…”
Section: Introductionmentioning
confidence: 99%